On the Composition of Public Spending and Taxes - George Economides; Hyun Park; Apostolis Philippopoulos; Stelios Sakkas (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper studies the implications of changes in the fiscal (spending-tax) policy mix when all categories of spending and taxes are according to their functional breakdown. In so doing, we build a general equilibrium OLG model which naturally incorporates the main functional categories of public spending and taxes as in the euro area. Departing from the crisis year of 2008, the main result is that an increase in public spending on education and health would have outperformed all other changes in fiscal policy that have either happened or have been debated in policy circles.
Keywords: H50; E60; 330; government expenditure; public finance